A (des)securitização de identidades pela União Europeia: a ambivalência da gestão fronteiriça das crises de refugiados síria (2016) e ucraniana (2022) - Osaki, Rafaela Claudino (2025)
This research aims to assess the European Union's measures to address the Syrian (2016) and Ukrainian (2022) refugee crises in light of the ambivalence of border management, raising the hypothesis of “(de)securitization of identities”. To this end, this work draws on the dialogue between the Copenhagen School's Securitization Theory (1998) and its contemporary reinterpretations of the securitization of migration in “Fortress Europe” to conduct an exploratory-procedural analysis of this case study. The qualitative approach adopted considers the continuum of (in)security that permeated the implementation of the European UnionTurkey Agreement and the Temporary Protection Directive in response to mass displacement, drawing on a literature review, documentary analysis, and the critical perspective of identity and cultural studies. This is because, although both measures are considered forms of externalization of external borders, the EU-Turkey Agreement implied the exclusion of migrants and refugees, while the TPD promoted the prompt reception of Ukrainians, questioning the ambivalence of border management externalized by the European Union: sometimes exclusionary, sometimes inclusive. This theoretical-conceptual dialogue was guided by the movements of securitization and desecuritization of migration, with a focus on Copenhagen's societal (in)security, whose identity keys of “Us” and “Other” are activated by border control through criteria of belonging and differentiation. As a result, the (de)securitization of identities by the European Union was observed, which instrumentalizes identity dynamics to justify measures of containment, profiling, and exclusion, especially of vulnerable and racialized minorities from the Geopolitical South, in favor of its political interests, contributing to the reproduction of the continuum of (in)security to the detriment of the guarantee of fundamental rights and the rule of law